Efikasi Herbisida Penoksulam pada Budidaya Padi Sawah Pasang Surut untuk Intensifikasi Lahan Suboptimal - Dwi Guntoro; Karlin Agustina; Yursida Yursida (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
An experiment on herbicide Penoksulam 25.5 g/L was conducted in tidal land. The objectives of this experiment was to determine the effectiveness of herbicides in controlling weeds in lowland rice. The experiment was conducted from November 2012 to March 2013. Randomized block design (RBD) with 6 treatments and 4 replications was used. The treatments tested the herbicide Penoksulam 25.5 g/L dose of 0.60 L/ha, 0.75 L/ha, 0.94 L/ha, 1,125 L/ha, manual weeding and control. The experimental unit was a plots measuring 5 m x 5 m. The results showed that the application of penoksulam 25.5 g/LÂ could to control weeds of lowland rice. Dominance weeds species in tidal land were Fimbristylis littoralis, Ludwigia octovalvis and Cyperus Iria. Application of herbicide at doses 0.60 L/ha up to 1.125 L/ha caused only mild symptoms of phytotoxicity on rice. Herbicides could be used to increase low land rice production on effective dose 0.60 L/ha to 0.75 L/ha.